2012
DOI: 10.1073/pnas.1121309109
|View full text |Cite
|
Sign up to set email alerts
|

Complement factor H genotypes impact risk of age-related macular degeneration by interaction with oxidized phospholipids

Abstract: The rs1061170T/C variant encoding the Y402H change in complement factor H (CFH) has been identified by genome-wide association studies as being significantly associated with age-related macular degeneration (AMD). However, the precise mechanism by which this CFH variant impacts the risk of AMD remains largely unknown. Oxidative stress plays an important role in many aging diseases, including cardiovascular disease and AMD. A large amount of oxidized phospholipids (oxPLs) are generated in the eye because of sun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
118
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(130 citation statements)
references
References 46 publications
(57 reference statements)
2
118
0
Order By: Relevance
“…CFH exhibiting the AMD risk 402H polymorphism was found to bind malondialdehyde or POVPC with less affinity than the CFH 402Y nonrisk variant (Weismann et al 2011;Shaw et al 2012). These independent studies also reported that inflammatory responses stimulated by malondialdehyde and POVPC in vitro and in vivo were stronger with the AMD risk variant of CFH than with the nonrisk CFH isoform, suggesting that the nonrisk isoform may help dampen inflammatory responses induced by oxidative modifications.…”
Section: Oxidative Protein Modifications In Drusensupporting
confidence: 51%
See 2 more Smart Citations
“…CFH exhibiting the AMD risk 402H polymorphism was found to bind malondialdehyde or POVPC with less affinity than the CFH 402Y nonrisk variant (Weismann et al 2011;Shaw et al 2012). These independent studies also reported that inflammatory responses stimulated by malondialdehyde and POVPC in vitro and in vivo were stronger with the AMD risk variant of CFH than with the nonrisk CFH isoform, suggesting that the nonrisk isoform may help dampen inflammatory responses induced by oxidative modifications.…”
Section: Oxidative Protein Modifications In Drusensupporting
confidence: 51%
“…Other lipoxidation products in drusen appear to be ligands for CFH, including malondialdehyde (Weismann et al 2011) and 1-palmitoyl-2-(5 0 -oxo-valeroyl)-sn-glycero-3-phosphocholine (POVPC) (Shaw et al 2012). CFH exhibiting the AMD risk 402H polymorphism was found to bind malondialdehyde or POVPC with less affinity than the CFH 402Y nonrisk variant (Weismann et al 2011;Shaw et al 2012).…”
Section: Oxidative Protein Modifications In Drusenmentioning
confidence: 99%
See 1 more Smart Citation
“…2D). Because vitamin A dimers, oxidized lipids, and lipoproteins are all implicated in the pathogenesis of macular dystrophies (8,10,18), our data point to excess cholesterol as a common etiological factor that could link these insults with abnormal complement activation in the outer retina.…”
Section: Resultsmentioning
confidence: 96%
“…The complement cascade is activated by insults that disturb RPE homeostasis, including defective clearance of phagocytosed photoreceptor outer segments (6) and abnormal accumulation of vitamin A dimers (7)(8)(9) or oxidized lipids (10) in the RPE. Studies also show that exposure to sublytic levels of MAC alters RPE barrier integrity, causes mitochondrial stress, and induces secretion of VEGF and proinflammatory cytokines (11,12).…”
mentioning
confidence: 99%